Most Probable Number of Coliform on Beef from Krian Abattoir, Sidoarjo - Pratiwi, Sambang Dewi; Harijani, Nenny; Sarudji, Suryanie; Budiarto, Budiarto; Estoepangestie, Soelih (Journal of Basic Medical Veterinary, 2022)
The problem on food health is the high amount of bacterial contamination of food served by food industries. The quality of beef can be affected by the level of bacterial contamination in meat. Coliform is a group of bacteria used as a sanitary hygiene indicator. The purpose of this study is to measure the value of MPN Coliform in beef at Krian's abattoir of district Sidoarjo. Thirty samples were taken from the abattoir of Krian, Sidoarjo. Most Probable Number was used to determine the level of Coliform's contaminate beef. The results showed that all beef samples at abattoir were contaminated with Coliform. The average contaminant levels was 706,76 MPN/g. Twenty six samples exceed the maximum limit of Coliform bacteria contamination in accordance with Indonesian National Standard (SNI). The highest Coliform MPN value is â‰¥ 1600 MPN / g, whereas the lowest MPN Coliform value is 8 MPN/g.